CYBER SECURITY AND THE CUSTOMS AGENCIES : CASE OF CAMEROON CUSTOMS ADMINISTRATION (CCA) - Dr. ALOUMEDJO ZAM Thierry Farrel (International Journal of Research Science and Management, 2024)
The aimed of our study is to evaluate the impact of cyber customs on its performance after identifying how and why it should be put in place in the CCA. This research is important considering the fact that Cameroon Customs administrations is facing serious challenges and the bugetary assigned target to the said administration by Government is above 1 000 billions FCFA in 2024. The problem Statement is to question the shortcomings of the incumbent CCA, Why can cyber customs correct the observed gaps, How can we put in place an efficient cyber customs in the CCA and What could be the various recommandations that can be made. The objectives were to identify what is cyber customs and how it can be put in place in the CCA ; determine its strong holds and possible limits and formulate recommandations to guarantee its sound application. Our work present three main interests which are managerial, theoretical and methodological. Four theories guided our analysis i.e. rational choice theory, Institutional Anomie Theory, strain theory and routine activity theory. We came out with the main results that there is no specific customs unit specialized in fighting cyber crimes as it is the case of the Customs Enforcement (ICE) that have special divisions dedicated to combating cyber crime. As far as electronic crime is concerned, Customs administrations need to be properly equipped and further trained as far as the legal and technological aspects are concerned in order to deal with sophisticated offences committed in cyberspace and which pose a great many challenges. Therefore the novelty of our research is the need of creation of a specific customs unit specialized in fighting cyber crimes in the CCA. The vision Statement of cyber customs being to enhance the nation’s security through innovation, intelligence, collaboration and trust in a context of the CCA becoming a member of the defense and security community alongside Police, army, gendarmerie, territorial administration, etc.